Radio spelling colombian university Radio - Zambrano Ayala, William Ricardo (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
The use of Information and Communication Technologies (ICTs) in university radio has been affecting programming, narratives, languages, soundscapes and habits of audiences. The study explores several strengths and weaknesses faced by Colombian university radio stations on the development of ICTs while integrating new tools, contents, narratives, interactive spaces, working methods and languages previously separated. For this purpose, I developed a descriptive exploratory research, using surveys, focus groups and in-depth interviews with the actors of these radios, in order to raise new proposals to addressing the major challenges of digital convergence and its implications on the development of university radio. Significant differences were observed in those university radios still using traditional models and those who were facing new changes. The recommendations are aimed to strengthen the new content, programming formats and audience profiles with universal access, to allow these stations to become actually an important platform for their presence and impact on society.